Food and nutrition security definitions, constructs, frameworks, measurements, and applications: global lessons - Pérez-Escamilla, Rafael (Frontiers in Public Health, 2024)
Food security (FS) is a powerful social determinant of health (SDOH) and is crucial for human and planetary health. The objectives of this article are to: (i) provide clarity on the definitions of FS, nutrition security; (ii) provide a framework that clearly explains the links between the two constructs; (iii) summarize measurement approaches, and (iv) illustrate applications to monitoring and surveillance, policy and program design and evaluation, and research, mainly based on the ongoing rich experience with food insecurity (FI) scales. A clear and concise definition of FI and corresponding frameworks have been in place for over two decades. There are different methods for assessing directly or indirectly FI. The best method(s) of choice need to be selected based on questions asked, resources and time frames available. Experience-based FI measures disseminated from the USA to the rest of the world in early 2000's became a game changer for advancing FI research, policy, program evaluation, and governance. The success with experience FI scales is informing the dissemination, adaptation, and validation of water insecurity scales globally. The many lessons learned across countries on how to advance policy and program design and evaluation through improves FS conceptualization and measurement should be systematically shared through networks of researchers and practitioners.Nutrition security among individuals is determined by FS in combination with other SDOH including health care access, housing, and other basic needs such as water security (3,4,15). Food and nutrition security sits right at the intersection of public health and human rights as reflected in articles from the UN Charter on the Right to Adequate Food (16). See for example Articles 11 and 12, International Covenant on Economic, Social, and Cultural Rights (ICESCR); Children's rights to food , health, care, survival, and development; Articles 6, 24, 27 of the Convention on the Civil Rights of the Child (CRC) detailing the rights of mothers to adequate nutrition during pregnancy and lactation, Article 12.2 of the Convention on the Elimination of all forms of Discrimination Against Women (CEDAW). These articles reflect the universal, indivisible, interrelated, and interdependence of the human right to food.